Design of a red-emitter hybrid material for bioimaging: europium complexes grafted on silica particles - Mutti, A. M.G. [UNESP]; Santos, J. A.O. [UNESP]; Cavalcante, D. G.S.M. [UNESP]; Gomes, A. S. [UNESP]; Job, A. E. [UNESP]; Teixeira, G. R. [UNESP]; Pires, A. M. [UNESP]; Lima, S. A.M. [UNESP] (Elsevier, 2019)
A bottom-up approach was used to design a high luminescent biomarker composed of nanoparticles of silica grafted with Eu3+ complex, and the labeling of CHO-k1 ovary cells and gastrocnemius muscle cells was successfully observed in imaging tests. Spheroidal silica nanoparticles were prepared via the solgel method and then decorated with Eu3+ complexes in a sequence of reactions to form the final hybrid nanoparticles. The material was characterized by scanning electron microscopy (120 ± 19 nm), zeta potential (−15 mV), and photoluminescence (red emission with 32% quantum efficiency). The material exhibit high biocompatibility with CHO-k1 cells, as evidenced via the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) method. CHO-k1 cells cultivated in the presence of the hybrid were investigated by microscopy techniques, and an active mechanism of internalization via phagocytosis was evidenced. Fluorescence and confocal images indicated red emission distributed in the cytoplasm, and especially around the nuclei. While for the muscle cells also stained with the luminescent particles, a distribution near the membrane was observed. Thus, the designed system proved to be safe and appropriate for use in bioimaging assays.
Keywords: Biomarkers; Functionalization; Inorganic-organic hybrids; Lanthanides; Photoluminescence